Murray Douch performs traditional accordion tunes ; and, Hans Hofmann performs German traditional music at Bermagui in the Rob and Olya Willis folklore collection. - Douch, Murray, 1926-; Hofmann, Hans, 1919-; Willis, Rob, 1944- (1993)
Folkloric recording.
Recorded on 7 January 1993 at Bermagui, N.S.W.
Digital master available
National Library of Australia ORAL TRC 2608/11.
National Library of Australia ORAL TRC 2608/13-14.
Keywords: Douch, Murray, -- 1926- -- Interviews; Hans Hofmann, -- 1919- -- Interviews; Accordionists -- New South Wales -- Bermagui -- Interviews; Folk musicians -- New South Wales -- Bermagui -- Interviews; Accordion music; Folk music -- Australia; Folk music -- Germany